THE CORRELATION BETWEEN THE KNOWLEDGE AND ATTITUDES OF PREGNANT WOMEN TOWARDS TETANUS TOXOID (TT) IMMUNIZATION - Mariatul Kiftia; Martina Martina (Journal of Public Health Science, 2025)
This study aims to determine the relationship between the level of knowledge and attitudes of pregnant women towards tetanus toxoid (TT) immunization in Banda Aceh City. The research method used is quantitative research with a cross-sectional analytical design. This study was conducted in three community health centers in the working area of ​​Banda Aceh City, namely Ulee Kareng, Kopelma Darussalam, and Meuraxa, with a sample of 107 pregnant women selected using a purposive sampling technique. Data were collected using a structured questionnaire that measured the characteristics of respondents, their level of knowledge, and their attitudes towards TT immunization, then analyzed using the chi-square test. The results showed that most respondents had sufficient knowledge (52.3%) and a positive attitude towards TT immunization (72.0%). The results of the bivariate analysis showed a significant relationship between the knowledge and attitudes of pregnant women towards tetanus toxoid immunization with a p value = 0.001. The conclusion of this study is that there is a significant relationship between the level of knowledge and attitudes of pregnant women towards tetanus toxoid (TT) immunization, where the better the knowledge of pregnant women, the more positive their attitudes towards the implementation of TT immunization.   Keywords: Knowledge, Attitudes, Pregnant Women, Tetanus Toxoid Immunization, TT